Teacher’s Attitude of School Learning Action Cell (SLAC) and Students’ Perception Towards Mathematics - Maga-Vasquez, Juliet J. (International Journal of Research in Interdisciplinary Studies, 2025)
The School Learning Action Cell (LAC) is a group of teachers in the Philippine Department of Education (DepEd) system that meets for collaborative learning to address common teaching challenges, share best practices, and enhance instruction and student learning, thereby functioning as a school-based professional development community focused on action and results. This descriptive study explored teachers' attitudes and students' perceptions towards mathematics among 17 junior mathematics teachers and 394 junior high students. A researcher made instrument, consisting of three parts, served as the primary tool for data collection. The findings revealed that all the grade levels were represented, with Grade 7 forming the largest group. The study further revealed that student learning in mathematics was not significantly affected by age, gender, daily allowance, or grade level. However, a positive teacher attitude toward SLAC significantly improved students’ perception, and teachers expressed strong appreciation for the professional benefits of SLAC, while students showed positive and negative perceptions towards mathematics.